Mass transport in a partially filled horizontal drum: Modelling and experiments - Tada, Érika Fernanda Rezendes; Bück, Andreas; Tsotsas, Evangelos; Thoméo, João Cláudio (Chemical Engineering Science, 2020)
This work presents a one-phase two-dimensional model describing the mass transport in an isothermal horizontal drum partially filled with silica beads and sugar cane bagasse (SCB), with air flowing in parallel to the bed surface, aiming further applications to solid-state cultivation processes (SSC). The effective diffusivities (Deff) of silica and SCB beds were experimentally determined, as well the equilibrium moisture content of the solids. Deff was of 1.67 10−9 m2/s for the silica bed and 29.2 10−9 m2/s for SCB. Classical correlations were applied to estimate the theoretical effective diffusivity in a bed of spherical (silica beads) and cylindrical (SCB) particles. Experiments were carried out in a still horizontal drum with filling degree 0.5 using low and high air flow rates and good agreement was noted between experimental and simulated results. The results obtained will be of help to model SSC processes in horizontal drums in a more realistic basis.
CRIS-Team Scopus Importer:2020-01-03
Keywords: Effective diffusivity; Horizontal drum; Mass transfer; One-phase model; Sugar cane bagasse